Spectrum of neuropsychiatric symptoms in chronic post-stroke aphasia - Edelkraut, Lisa; López-Barroso, Diana; Torres-Prioris, María José; Starkstein, Sergio E.; Jorge, Ricardo E.; Aloisi, Jessica; Berthier-Torres, Marcelo Luis; Dávila-Arias, María Guadalupe (Baishideng Publishing Group, 2022)
BACKGROUND: Neuropsychiatric symptoms (NPS) are understudied in persons with aphasia (PWA) since most research excludes those with language disorders. AIM: To present a two-part study including a literature review and an observational study on NPS in post-stroke aphasia. METHODS: Study 1 reviewed articles from PubMed, PsycINFO, Google Scholar, and Cochrane using keywords linking post-stroke aphasia to NPS. Study 2 evaluated 20 PWA (median age: 58; range: 28–65; 13 men) with the Western Aphasia Battery-Revised and the Barthel Index. Informants completed the Neuropsychiatric Inventory and domain-specific scales (Stroke Aphasia Depression Questionnaire-10, Starkstein Apathy Scale), while PWA were directly assessed with an adapted Hospital Anxiety and Depression Scale. The study corresponds to the baseline assessment of an intervention trial (EudraCT: 2017-002858-36; NCT04134416). RESULTS: The review identified diverse NPS in PWA, including depression, anxiety, apathy, agitation, eating and sleep disorders, psychosis, and hypomania, emphasizing the need for better assessment and treatment. In Study 2, participants showed mild-to-moderate aphasia and functional independence but multiple comorbid NPS (median: 5; range: 1–8). Most exhibited depressive symptoms (75%), agitation/aggression (70%), irritability (70%), anxiety (65%), and appetite/eating issues (65%); apathy appeared in 50%, and euphoria or psychosis in 5%. Domain-specific scales revealed 45% apathy and 30% depression and anxiety. CONCLUSION: Co-occurring NPS are frequent in chronic post-stroke aphasia, highlighting the need for reliable diagnostic tools and tailored therapeutic approaches.
Keywords: Afasia; Enfermedad cerebrovascular - Complicaciones y secuelas; Aphasia; Stroke; Neuropsychiatric symptoms; Anxiety; Apathy; Depression